2010
DOI: 10.1002/sia.3355
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of thin and ultrathin transparent conducting oxide (TCO) films and TCO‐Si interfaces with XPS, TEM and ab initio modeling

Abstract: Interfaces play an important role in solar cell heterostructures, especially when film thicknesses decrease. In this work, we use XPS, transmission electron microscopy (TEM) and density functional theory (DFT) to study both the film and the film-Si interface of electron beam deposited indium tin oxides (ITO) and pulsed laser deposition (PLD) deposited ZnO on p-Si (100). Vacuum evaporation of ITO resulted in a film that contained elemental Sn and In which oxidized after annealing at 300• C for 30 min. Ar etchin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…31,32 It is furthermore known that Sn segregates to the surface of Sn-doped In 2 O 3 , 33 and that metallic Sn-In in ITO can be formed after heat treatment, 34 as well as upon electron beam evaporation. 31,35,36 In the case of e-beam deposition, the amount of metallic In present in the amorphous as-deposited film decreases with increasing the incident angle of the ITO vapour to the Si substrate, with increasing the deposition temperature and/or the post deposition annealing temperature, as well as with reducing the deposition rate. 35,36 In a number of studies, the Si-ITO interface has been studied experimentally; see Refs.…”
Section: B Ito-si Interfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…31,32 It is furthermore known that Sn segregates to the surface of Sn-doped In 2 O 3 , 33 and that metallic Sn-In in ITO can be formed after heat treatment, 34 as well as upon electron beam evaporation. 31,35,36 In the case of e-beam deposition, the amount of metallic In present in the amorphous as-deposited film decreases with increasing the incident angle of the ITO vapour to the Si substrate, with increasing the deposition temperature and/or the post deposition annealing temperature, as well as with reducing the deposition rate. 35,36 In a number of studies, the Si-ITO interface has been studied experimentally; see Refs.…”
Section: B Ito-si Interfacesmentioning
confidence: 99%
“…39 Recent studies employing a combination of transmission electron microscopy (TEM) and XPS on thin and ultra-thin ITO films deposited on Si have shown the formation of a mixed In-Si oxide along the ITO-Si interface where Si does not participate in its formal stoichiometry (i.e., SiO 2 ). 31 Ex-situ XPS and TEM studies 41 on ITO films deposited on p-Si (100) substrates by dc magnetron sputtering revealed the presence of amorphous In clusters at the interface associated with oxygen deficiency in the ITO film. A recent in-situ XPS study 42 (similar to the one presented in this paper) of ITO grown on p-Si showed the presence of elemental In and Sn as well as Si sub-oxides.…”
Section: B Ito-si Interfacesmentioning
confidence: 99%
“…Three peaks at 529.9, 531.1 and 533.6 eV are assigned to O 2− , carbonyl group (C O), and (C-O) or Sn-O, respectively [46][47][48]. In ITO films, the low binding energy O 1s component at 529.9 eV is attributed to oxygen in the form of oxide, O 2− present on ITO surface [49,50]. Carbonyl group (C O) peak is the strongest signal among them.…”
Section: Effect Of Molecular Dipole On Ito Work Functionmentioning
confidence: 99%
“…An in situ x-ray photoelectron spectroscopy study of the initial stages of rf magnetron sputter deposition of indium tin oxide on p-type Si substrate M. H. Rein, 1,a) M. V. Hohmann, 2 A. Thïgersen, 3 J. Mayandi, 4 A. O. Holt, 1 A. Klein, 2 and E. V. Monakhov 1,5 Despite the growing number of available transparent conducting materials (TCMs), indium tin oxide (ITO) is still the most preferable TCM for a number of applications due to its excellent electrical and optical properties. 1 When ITO is deposited on a Si substrate a thin (1-3 nm) silicon oxide (SiO x ) layer is established, due to the thermodynamics of this formation.…”
mentioning
confidence: 99%
“…Chemical analysis of bonds between elements in an ITO/Si interface is previously carried out by the use of ex situ XPS of ultrathin ITO films on monocrystalline Si and XPS depth profiling of ITO on monocrystalline silicon and amorphous silicon. [5][6][7] XPS is a characterization method which is sensitive to surface contamination. For instance, carbon impurities are previously proven to affect the work function value of ITO measured by XPS.…”
mentioning
confidence: 99%